Wheat gluten and spray-dried plasma protein blends for nursery pigs - L L Burnham; I H Kim; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
Using a 50:50 blend of spray-dried plasma protein (SDPP):spray-dried wheat gluten (WG) (i.e., with each as approximately 4% of the diet) gave the greatest ADG and ADFI, while reducing diet costs compared to the control diet (i.e., 8% SDPP). Even with a slight decrease in efficiency of gain, the marked decrease in diet cost will yield better cost of gain with a 50:50 blend versus using only SDPP.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Nursery; Wheat gluten; Plasma protein